Clown-guia: Uma vivência palhacesca guiada pela noção de performatividade - Silva, Salu Salustiano (2021)
This master's thesis describes a research trajectory and analyzes a course taught under my authorship called Clownery Introduction. The methodological proposal used the concept of unformation proposed by Wuo (2016) as the guiding pillar of the practices - developed in the process with a group of collaborating artists, who underwent exercises and games aimed to comicality. The objective of the research was to develop a methodology to comicality initiation with an emphasis on clown performance, aiming to the blossoming of clown’s basic principles among collaborators. The investigative methodology was supported by the perspective of Somatic-Performative Research developed by Ciane Fernandes (2014), favoring the development of practices and making the entire textual structure anchored and based on the living experience. It was found, during the writing and analysis of the work that, despite presenting positive results from the proposed games, my lack of experience in the clown universe revealed some gaps related to the initiation and training of collaborators. A while later, after completing the Clownery Introduction course, I was initiated as a clown by Ana Elvira Wuo on the discipline “Special Topics in Poetic Practices”, taught by the professor in the Theater Course at the Federal University of Uberlândia – remotely promoted in the second stage of the AARE. My perspectives changed from that, making me understand that my training proposal would be more suitable to add playful experiences to clowns previously initiated. The research revealed that in order to initiate clowns, the trainer needs an introduction to the rites of passage with deepening consistent on theoretical methodological bases anchored on preliminary experiences.